Age-group-specific associations between adenoid/tonsillar hypertrophy and craniofacial features - Liping Huang; Liyuan Zheng; Xiaobo Chen; Yuming Bai (BMC, 2024)
Abstract Background Age plays an important role in the association between adenotonsillar hypertrophy and craniofacial morphology. This study aimed to analyse the association of adenoid and tonsillar hypertrophy with craniofacial features in different age groups. Methods Lateral cephalograms were obtained from 942 patients aged 6-15 years (433 boys, 509 girls). They were divided into three age groups: 6-9 years (n = 189), 9-12 years (n = 383), and 12-15 years (n = 370). According to the different sites of pharyngeal obstruction, they were classified as control group (CG), adenoid hypertrophy group (AG), tonsillar hypertrophy group (TG) and adenotonsillar hypertrophy group (ATG). Cephalometric measurements were performed on each enrolled participant. Comparisons between groups and correlations between these cephalometric variables and obstruction sites were evaluated. Results At 6-9 years of age, ATG and TG correlated with increased mandibular height (B = 2.2, p = 0.029; B = 2.6, p = 0.042, respectively). At the age of 9-12 years, AG showed a steep growth direction (B = 1.5, p = 0.002), TG showed a higher probability of Class III skeletal pattern (smaller SNB, ANB and SGn/FH, larger Go-Me) and ATG manifested a higher proportion of Class III skeletal pattern. At 12-15 years of age, there was no significant association between cephalometric measurements and pharyngeal lymphoid tissue enlargement. Conclusions Children with isolated adenoid hypertrophy have a vertical growth direction at 9-12 years of age. Isolated adenoid hypertrophy correlated with longer mandibular body, more anterior mandible and horizontal skeletal Class III pattern at 6-12 years. Combination of obstructive adenoids and tonsils manifested similarly to children with isolated tonsil hypertrophy.